The Mosquitoes of Morelos, Mexico: DNA Barcodes, Distribution, Ecology and the Resurrection of the Name Culiseta dugesi Dyar and Knab (Diptera: Culicidae) - Ortega-Morales, Aldo I.; Garza Hernandez, Javier Alfonso; Hernández-Triana, Luis M.; Ramírez-Huicochea, Carlos M.; Martínez-Gaona, Andrés J.; Quijano-Barraza, J. Manuel; González-Acosta, Cassandra; Correa-Morales, Fabián (2024)
To update the record of mosquito diversity in the state of Morelos, Mexico, mosquito collections were conducted in both physiographical regions of Morelos: the Neo-volcanic Axis and the South Mountain Range. Immature stages were collected from aquatic habitats, while adult mosquitoes were collected using CDC light traps, Shannon traps and approaching/landing on the collecting personnel. All specimens were identified using taxonomic keys and the mitochondrial cytochrome C oxidase subunit 1 (COI). Following Mexico State, this is the second study of mosquito taxonomy of a complete Mexican state using COI barcoding. In Morelos, a total of 58 species of mosquito occurs, of which we report 12 for first time (Aedes vexans, Ae. euplocamus, Ae. vargasi, Psorophora cilipes, Ps. lineata, Culex restrictor, Cx. interrogator, Cx. nigripalpus, Cx. tarsalis, Cx. sandrae, Cx. lactator and Toxorhynchites moctezuma). Morelos now ranks sixth in mosquito diversity among Mexican states. Phylogenetic trees were constructed for 32 species, including Ae. shannoni, which is a new record for GenBank databases. Additionally, we report COI barcode sequences of Culiseta dugesi Dyar and Knab, which is resurrected from the synonymy of Cs. particeps (Adams). Fourth instar larvae and adult females of Cs. dugesi were redescribed. This brings the number of mosquito species in Mexico to 248. Ecological and distributional notes for the new records, the medical importance of mosquito species in Morelos, and an identification key for larvae and females of the known Culiseta species occurring in Mexico are also included.